PERBANDINGAN METODE CRITICAL PATH METHOD (CPM), PRECEDENCE DIAGRAM METHOD (PDM), DAN LINE OF BALANCE (LOB) TERHADAP PROYEK REPETITIF - Joe Daniel Hutagaol; Sendi Sendi; M. Agung Wibowo; Tanto Djoko Santoso (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Today the rapid development of the construction project running and often in large-scale costly and have a method that can improve the quality of planning and control to deal with the number and complexity of the project activities are likely to increase. The contractors are often faced with projects that contain identical or similar multiple units, such as segments on the flo or of multistory buildings, housing units in the residential development, and road sections in road projects. The purpose of this study is to compare and determine the critical path of Critical Path Method, Precedence Diagram Method, and Line of Balance to find the appropriate scheduling method character for the repetitive project and compare each method in terms of the method using, the production calculation speed, the dependence logic, the constraints on the activities, and analyze the advantages and lacks. The analysis process is done by comparing the Critical Path Method, Precedence Diagram Method, and Line of Balance for building and road projects. From the results of the literature study and data analysis are found the lacks and advantages visually that is Critical Path Method and Precedence Diagram Method has a more complex visual display so it is not easy to understand and can not directly detect impaired activities in project scheduling. But can show you specific logical dependency relationships between the activities and projects can determine the critical path. Line of Balance has a visual display that is simple and 2 easy enough to understand. Line of Balance can also directly detect impaired activities in project scheduling, but Line of Balance can not point to specifically logical dependency relationships between activities and projects critical path.